ANALISIS PENGARUH BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN SAUNG IBU TANGERANG - Tjaya, Sherina Jeanita; Iskandar, Hari (LPPM Institut Pendidikan Nusantara Global, 2023)
With the emergence of various brands, consumers choose from many brands to ultimately buy a product from a brand. The purpose of this research is to find out how much influence brand awareness has on the decision to buy by consumers. This research was conducted at the Saung Ibu Restaurant, Tangerang. This study uses quantitative methods with data collection techniques through questionnaires. In this study the authors will conduct research on 120 respondents who are consumers who have made purchases at Saung Ibu Restaurant. The results of the respondents' answers will later be processed using SPSS version 25. Data analysis was carried out by validity, reliability, normality test, multicollinearity test, heteroscedasticity test, simple linear regression test, t test, f test, and coefficient of determination test (R2) in knowing how much influence brand awareness has on purchasing decisions and knowing which variables has the most dominant influence. Based on the results of the research that has been done, it can be concluded that the results of the simple linear regression test that has been carried out state that Brand Awarzeness (X) has an effect on the purchasing decision variable (Y). Then based on the results of the T test it can be concluded that there is a partial influence of the brand awareness variable (X) on the purchasing decision variable (Y). Furthermore, based on the results of the F test, it can be concluded that there is a simultaneous influence of brand awareness (X) on the purchase decision variable (Y). Based on the test of the coefficient of determination, it is known that the R square is 0.702, this means that the influence of the brand awareness variable (X) simultaneously on the purchase decision variable (Y) is 70.2%.